2017
DOI: 10.1111/jce.13127
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Women and Men Undergoing Catheter Ablation for Sustained Monomorphic Ventricular Tachycardia

Abstract: Although heart disease tends to present later in women, our data do not suggest that women are referred later than men. Women with CAD or NICM and VT present for ablation at younger age with disease severity comparable to men. VT ablation in women can be accomplished with success- and complication rates comparable to male patients in both those with and without SHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
1
28
0
3
Order By: Relevance
“…Hosseini et al [70] analyzed >500.000 performed ablations, including also atrial ablations, and found female sex as an independent predictor for complications. In contrast, Baldinger et al [16] did not find differences in success and complication rates between female and male patients in patients with and without structural heart disease (Fig. 3, Ref.…”
Section: Outcomes and Complicationsmentioning
confidence: 82%
See 3 more Smart Citations
“…Hosseini et al [70] analyzed >500.000 performed ablations, including also atrial ablations, and found female sex as an independent predictor for complications. In contrast, Baldinger et al [16] did not find differences in success and complication rates between female and male patients in patients with and without structural heart disease (Fig. 3, Ref.…”
Section: Outcomes and Complicationsmentioning
confidence: 82%
“…Fewer studies have investigated sex differences in patients with VA and structural heart disease that undergo catheter ablation. Baldinger et al [16] analyzed 948 consecutive patients undergoing 1314 catheter ablations for sustained monomorphic ventricular tachycardia (VT) over a span of 10 years. Of those 948 patients, 486 patients had ICM with only 9% of them being female and 301 patients had NICM with 22% of them being female.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In einer großen multizentrischen Registeruntersuchung [13] In einer anderen Registerstudie mit ca. 900 Patienten, von denen 18 % Frauen waren, konnte diese Tendenz zu schlechteren Ablationsergebnissen allerdings nicht nachvollzogen werden [14]. Hier handelte es sich um ein gemischtes Kollektiv aus idiopathischen und nicht idiopathischen VT, sodass ein Vergleich der beiden Studien schwierig ist.…”
Section: Ventrikuläre Tachyarrhythmien Bei Struktureller Herzerkrankungunclassified